Minimally Invasive Retrograde Method of Harvesting the Flexor Hallucis Longus Tendon: A Cadaveric Study. Issue 4 (16th October 2019) - Bull, Patrick; Goss, David; Halverson, Adam
Category: Ankle Introduction/Purpose: Utilization of the flexor hallucis longus (FHL) tendon is well described for several tendon augmentation procedures. Recently, several authors have described a minimally invasive (MI) technique to harvest the tendon utilizing a hamstring tendon stripper. The purpose of this study was to evaluate the safety and effectiveness of harvesting the FHL tendon utilizing this novel technique. Methods: The FHL tendon was harvested through a transverse plantar incision over the interphalangeal joint of the great toe in 10 fresh-frozen cadaver lower extremities. Complications, tendon length and interconnections between the FHL and flexor digitorum longus (FDL) were recorded. The specimens were then dissected by a single surgeon in a standardized fashion and damage to any surrounding structures was recorded. Results: The average length of the FHL tendon from the distal stump to the 1st inter-tendinous connection was 13.33 cm (range 8.8-16 cm, SD: 2.28 cm). Eight cadavers demonstrated Plaass Type 1 interconnections while 2 were Type 3. There was no injury to the medial and lateral plantar arteries or nerves, plantar plate or FDL tendons. One FHL tendon was amputated during graft harvesting. Conclusion: Care must be taken when approaching the sustentaculum with the tendon harvester in order to avoid amputation of the graft against a hard bony endpoint. Additionally, flexion and extension of the lateral toes can aid in successful tendon harvest when tendon interconnections are encountered. Utilizing this MI technique appears to be a safe and effective way to obtain a long FHL tendon graft tissue augmentation.